Service Learning: Staging Hispanic Theatre for Bilingual Elementary Students - Misemer, Sarah M. (Latin American Theatre Review, 2017)
“Staging Hispanic Theatre” is a service-learning course that exemplifies a pedagogical practice that Rita Irwin and colleagues term “a/r/tography”—a strategy in which arts-making, research, teaching, and learning take place simultaneously, benefitting students, instructors, and audiences. Undergraduate students engage in high-impact practices (HIP) as they study children’s theatre and pedagogy, and they use this knowledge to write and act in their own plays in Spanish for elementary school children in bilingual programs. Undergraduate students mentor and model behavior for elementary students in the target language and simultaneously develop their own linguistic, literary, and pedagogical skills. They provide cultural capital for children who may not be familiar with theatre practices and behavior, and they explore how language can be used to communicate in real-world settings and how a liberal arts education can be applied to understand existing works of literature and to create new compositions. With this essay, I also show how arts-making and teaching practices can overlap with and impact research.